SAFETY AND EFFICACY OF INTRA-ARTICULAR STEROID INJECTIONS IN OSTEOARTHRITIS OF THE KNEE – A PROSPECTIVE OBSERVATIONAL STUDY - BABY, MINU; KESAVAN, KALA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to assess the safety and efficacy of intra-articular steroid injections in osteoarthritis of knee. Methods: This prospective observational study was conducted for a period of 12 months in a tertiary care hospital. Patients were given intra-articular injections of triamcinolone hexacetonide 40 mg (1 cc) in the affected knee at the time of enrollment and thereafter at 6 and 12 weeks. The treatment response was evaluated based on the improvement in the various clinical scoring systems. Comparison of quantitative variables of successive follow-up with baseline value was analyzed. p < 0.05 was taken as level of significance. Results: Of the 106 patients included in the study, the mean age was 64.12±8.69 years. The mean 50 foot walking time improved from 13.85 s to 12.64 s (p=0.003) by 24 weeks. Range of motion improved from a mean of 126.75–131.63° (p=0.001). The physician’s global assessment score improved from a baseline mean of 54.42–46.39 while the patient’s global assessment score progressed from 57.8 to 46.38 both being statistically significant. Patient’s pain assessment score reduced from baseline mean value of 57.32–45.95 and nocturnal pain improved to 30.24 at 24 weeks from a baseline value of 36.51. The mean Western Ontario and McMaster Universities Osteoarthritis Index score improved to 45.93 from baseline of 56.92. Conclusion: Repetitive IA steroid injections appear to be safe with no significant deleterious effects on the anatomical joint structure.